The Urgency of Customary Criminal Law in the Framework of National Criminal Law Reform - Herry Liyus; Andi Najemi; Dheny Wahyudi (Jurnal Mamangan, 2026)
The enactment of Law Number 1 of 2023 on the Indonesian Criminal Code represents a significant transition from a colonial formal legality model toward a criminal law system that recognizes living law. This article examines the urgency of customary criminal law in national criminal law reform by focusing on the position of customary law as a source of substantive justice, the problem of formalizing customary offenses through regional regulations under Government Regulation Number 55 of 2025, and the constitutional safeguards required to prevent local criminalization that violates legal certainty and human rights. This study employs a qualitative normative legal method using statutory, conceptual, and limited socio-legal approaches. The findings show that customary criminal law is urgent as an instrument of legal decolonization, social equilibrium restoration, restorative justice, and the reconstruction of a Pancasila-based criminal law system. Nevertheless, its recognition must be limited by the existence of indigenous legal communities, compatibility with Pancasila and the 1945 Constitution, human rights protection, and procedural guarantees through regional regulations, review mechanisms, and judicial control. The novelty of this article is the proposed protective-responsive integration model that positions customary criminal law not merely as an exception to legality but as a corrective source for substantive justice in national criminal law reform.